Դեվշիրմե համակարգի սկզբնավորման հարցերի շուրջ - Շաքարյան, Արտակ («Զանգակ - 97»)
The urticle represents some basic questions regarding the inception of devshirme levy syslem, periodieal boy-tribute. taken from Christians in the Ottoman Empire in 15th - I6th centuries. Based on facts collected from Armenian medieval manuscripts. Ottoman documents, published in Bulgaria, as well as narrative sources, author analyses some main lactors, which influence was crucial for the inception of devshirme. Author concludes that tlic devshirme system was instituted in the newly occupied tcrritories only alter having practiced the pencik system, one-fifth tax, for а while, and that devshirme was not a brand new "invenlion" of some Ottoman sultans, ratlier, it was a further development of the pencik system.
Keywords: Պատմություն; Քաղաքականություն